Profiling withanolide A for therapeutic targets in neurodegenerative diseases. Issue 12 (15th June 2019) - Crane, Erika A.; Heydenreuter, Wolfgang; Beck, Katharina R.; Strajhar, Petra; Vomacka, Jan; Smiesko, Martin; Mons, Elma; Barth, Lydia; Neuburger, Markus; Vedani, Angelo; Odermatt, Alex; Sieber, Stephan A.; et al.
Graphical abstract: Abstract: To identify new potential therapeutic targets for neurodegenerative diseases, we initiated activity-based protein profiling studies with withanolide A (WitA), a known neuritogenic constituent of Withania somnifera root with unknown mechanism of action. Molecular probes were designed and synthesized, and led to the discovery of the glucocorticoid receptor (GR) as potential target. Molecular modeling calculations using the VirtualToxLab predicted a weak binding affinity of WitA for GR. Neurite outgrowth experiments in human neuroblastoma SH-SY5Y cells further supported a glucocorticoid-dependent mechanism, finding that WitA was able to reverse the outgrowth inhibition mediated by dexamethasone (Dex). However, further GR binding and transactivation assays found no direct interference of WitA. Further molecular modeling analysis suggested that WitA, although forming several contacts with residues in the GR binding pocket, is lacking key stabilizing interactions as observed for Dex. Taken together, the data suggest that WitA-dependent induction of neurite outgrowth is not through a direct effect on GR, but might be mediated through a closely related pathway. Further experiments should evaluate a possible role of GR modulators and/or related signaling pathways such as ERK, Akt, NF-κB, TRα, or Hsp90 as potential targets in the WitA-mediated neuromodulatory effects.